USING RECIPROCAL MODEL IN TEACHING READING COMPREHENSION FOR THE TWELVE GRADE AT SMK KR. HARAPAN RANTEPAO - Delvianti Posi (Teaching English as a Foreign Language Overseas Journal, 2022)
The Objective of research is to find out whether the use of a reciprocal model in teaching reading comprehension for the twelve grade at SMK kr. Harapan Rantepao. The writer used quantitative experimental research. The population was the twelve grade students’ of SMK Kr. Harapan Rantepao in the academic year 2018/2019. There were 2 classes as a population. The writer used cluster sampling technique, by choosing one class as a respondent, namely the class XI TJK B. There were 20 students. The data collected through a written test. The result of comparison between students’ score in t-test and t-table indicated that there was a significant difference in improvement of students’ reading comprehension between the students who were taught by reciprocal model and those who were not. Based on the result of data analysis, the writer concluded that the reciprocal model is effectively used in teaching reading comprehension for twelve grade students at SMK Kr. Harapan Rantepao.